Impact of Public Capital Expenditure on Inflation Rate in Nigeria - Jideofor Nnennaya Joy; Michah Chukwuemeka Okafor; Eke Onyekachi Abaa (Newinera Publisher, 2021)
This paper examines the impact of public capital expenditure on inflation rate in Nigeria. The data for the study were sourced from various issues of the Central Bank of Nigeria’s statistical bulletin. The data was subjected to unit root test using Augmented Dickey fuller (ADF) approach to ascertain the time series properties. Descriptive statistics was used to assess the socioeconomic characteristics of the variables. Due to the mixed order of integration witnessed in the unit root, ARDL- Autoregressive Distributed Lag approach was used for cointegration and regression analysis. The result found that Public capital expenditure is negatively and statistically significant (tcal = -2.903) in influencing Inflation Rate in Nigeria. This outcome is highly directional in the sense that prudent and productive spending will always subdue inflation in any economy; therefore, this study recommend that government should increase its investment in production sectors and encourage skilful and willing citizens to participate, since this would reduce the expenses being incurred on business as a result low currency value and raise the profitability of firms.